Use of medication among nursing home residents: a Danish drug utilisation study. (7th March 2020) - Lundby, Carina; Jensen, John; Larsen, Søren Post; Hoffmann, Helene; Pottegård, Anton; Reilev, Mette
Abstract: Background: Data on drug utilisation patterns in nursing home populations is scarce. We aimed to describe drug use patterns in Danish nursing home residents. Methods: We established a cohort of 5, 179 individuals (63% women; median age of 84 years) admitted into 94 nursing homes across Denmark during 2015–2017. Data on prescription drug use and other census data were obtained from the nationwide Danish health registries. Results: The total number of drug classes filled increased from a median of 6 drugs (interquartile range [IQR] 3–9) at 18–24 months before nursing home admission to a median of 8 drugs (IQR 6–11) just after admission, with the most common drug classes comprising paracetamol (61%), platelet inhibitors (41%), proton pump inhibitors (34%), statins (33%) and potassium supplements (31%). The incidence rate of new drug treatments increased from 21 new treatments/100 residents/month at 12–24 months before admission to a peak of 71 new treatments/100 residents/month in the month prior to admission, while it levelled off to about 34 new treatments/100 residents/month after 6–9 months. The drug classes primarily responsible for this peak were laxatives, antibiotics and analgesics. The largest absolute increases were seen for laxatives (53%), paracetamol (43%) and antidepressants (36%), all showing a marked increase up to and following admission. A high proportion of residents remained on therapy in the 3-year period following admission, with users of antidepressants and antidementia drugs being most persistent. Conclusion: Nursing home admission is associated with an increase in use of both predominantly preventive and non-preventive drug classes.